Exploring weathering and erosion - Rogers, Marie, 1990- (New York : PowerKids Press, 2022)
Weathering is when rocks break down into sediment due to natural processes, while erosion is when natural agencies (such as wind and water) carry sediment to another place. This book explains the different types of weathering and erosion and how these processes work together. Information on how humans can combat these natural but destructive processes is also covered. Color photographs show weathering and erosion in action, while a diagram explains how they work together to create the world around us.
Earth's Landscapes -- Weathering -- Erosion -- In the Rock Cycle -- Danger! -- Speeding It Up -- Soil Erosion -- Changing the World.
Includes index.
3-6
7.0
Keywords: Weathering -- Juvenile literature; Erosion -- Juvenile literature; Weathering; Erosion; Earth sciences; Geology